Effect of Chemotherapy and Surgery on System Immune Function of Patients with Cervical Cancer - CHEN Yu; WANG Hui (Zhongliu Fangzhi Yanjiu, 2022)
Objective To explore the effects of chemotherapy and surgery on system immune function of patients with cervical cancer. Methods Data of patients with cervical cancer diagnosed by pathology were retrospectively analyzed. Fasting blood samples were drawn from all patients and sent for immune function testing before treatment, 3 weeks after 1-4 cycles of chemotherapy, and 3-7 days after surgery. The patients were grouped according to age, FIGO stage, pathological type, histological grade, and HPV infection state. Kruskal-Wallis test was used to analyze factors influencing the absolute value count of peripheral blood lymphocytes before treatment. Bonferroni test was used to compare the differences between subgroups. The data of a patient before and after treatment were analyzed by Wilcoxon signed-rank test. Results The immune function of patients with cervical cancer before the treatment was related to age (P < 0.001) and pathological type (P=0.023). The humoral immunity decreased after chemotherapy (P=0.012). The cellular immunity decreased after chemotherapy with D1, 8 regimen (P < 0.05), while the cellular immunity increased after chemotherapy with D21 regimen (P < 0.05). Within one week after the operation, the system immune function decreased significantly (P < 0.001). Laparoscopic surgery had a more significant inhibitory effect on system immune function than open surgery (P < 0.001). Conclusion The immune function of patients with cervical cancer before treatment is affected by age and pathological type. It decreased after 3 weeks of chemotherapy or within one week after the operation. Different chemotherapy regimens or surgical approaches have different effects on immune function.